Obtaining of surface-active substance sorbents based on acrylate-clay polymers (International Journal of Biology and Chemistry, 2017)
In this work the problem of sewage treatment containing surface-active substance (SAS), using polymer-bentonite clay (BC) was discussed and sorbent synthesized. The sorption capacity of obtained polymer-clay composites in relation to surfactant in different environments and conditions was estimated. The used bentonite clay of the Manyrak deposit (East Kazakhstan region) was purified with the help the method of Salo by repeated washing with distilled water. Chemicallу cross-linked composite gels based on bentonite claу and polуcarboxуlic acids – poyacrylic (PAA) and polymethacrylic acids (PMAA) in ratio 1:10, 3:10 and 5:10 were sуnthesized with adding cross-linking agent methylene-bis-acrylamide (MBAA) 1 mole %, dinitrile of azo-bis-isobutyric acid (DAA) 0.5 mole % by weight of the monomer at a temperature of 70 °C for 2 hours. The kinetics of swelling of obtaining composites in solutions of and cationic surfactants – cetylpyridinium bromide (CPB), cetyltrimethylammonium bromide (CTAB) were studied; the influence of internal factors: the content of clay, concentration of surfactants, temperature and pH of the medium, on the swelling of composites in surfactant solutions was examined. These studies were carried out on a scanning electron microscope Quanta 3D 200i Dual system, Leica DM 6000 M (Switzerland) digital optical microscope for obtaining the morphological structure of dry and swollen samples of the obtained compositions, IR spectrometer «Satelitte» FTIR Mattson (USA), and Radwag AS 220/X (Poland) for measuring the densitу.